A Double-Blinded Randomized Controlled Study on the Effectiveness of Postoperative Analgesia-Comparison Between Ultrasound Versus Anatomical Landmark Technique of Blocking Bilateral Supra Zygomatic Maxillary Nerve in Paediatric Patients Undergoing Cleft P - Subashini Vichili Mohan , Gayathri Balasubramaniam, Gunaseelan Mirunalini (South Eastern European Journal of Public Health, 2025)
Introduction: Cleft palate requires surgical correction between 9-18 months of age, often involving palatoplasty techniques. This study aimed to compare the effectiveness of postoperative analgesia between ultrasound-guided suprazygomatic maxillary nerve block and anatomical landmark technique in patients undergoing cleft palate repair. Methods: This double-blind, randomised controlled study included 70 paediatric patients at the SRM Medical College Hospital between April 2023 and March 2024. The children were randomly assigned to either the US or LM group. Anesthesia was induced, and a suprazygomatic maxillary nerve block was performed using either landmarks or ultrasound. Postoperatively, pain was assessed every 2 h for 24 h using the FLACC score, and intravenous paracetamol was administered if the score exceeded 5. Results: There were no significant differences in sex, height, weight, airway assessment, ASA of Anesthesiologists status, or surgery duration between groups (p>0.05). The US group had a significantly longer block administration time than the LM group did. The US group also showed a statistically significant reduction in the postoperative mean arterial pressure from 1 to 24 h and a lower heart rate. FLACC scores were significantly lower in Group US at 30 minutes, 2, 4, and 8 hours, indicating better pain management and longer block duration (13.08±1.70 vs. 10.80±3.53 hours). Patients in the US group required postoperative rescue analgesics (22.9 vs 45.7%; p=0.044). Conclusion: Children who underwent cleft palate repair experienced superior pain relief with ultrasound-guided suprazygomatic maxillary nerve block, and analgesic efficacy was enhanced by the addition of 0.3 μg/kg to 0.2% ropivacaine.